Unemployment and personality: Are conscientiousness and agreeableness related to employability? - Carina Engelhardt (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper shows that unemployment and (some) personality traits are related. Individuals with low scores in the Big Five dimensions conscientiousness and agreeableness have a higher probability of being unemployed, longer unemployment durations, and experience more status changes between employment and unemployment. Results suggests that personality is an important determinant of women's risk of unemployment, but for men personality is more a matter of job keeping.
Keywords: H53; D31; J64; C38; 330; Noncognitive skills; Personality; Unemployment; Factor models